X-ray radiation effect of C-arm on adipose tissue-mesenchymal stem cell viability and population doubling time (Medical Journal of Indonesia, 2016)
Background: Adipose tissue derived mesenchymal stem cells (AT-MSCs) are relatively easy in isolation procedure compared to bone marrow-derived. Minimally invasive MSC injections need C-arm as guidance that potentially influence the cell viability and doubling time. This study aimsed to determine the effect of C-arm X-ray exposure on AT-MSC viability and population doubling time (PDT). Methods: This experimental study used cryopreserved adipose tissue derived MSCs stored in Stem Cell Medical Technology Integrated Service Unit Cipto Mangunkusumo Hospital. Cells were thawed, propagated, and exposed to varying doses of C-arm X-ray radiation. Stem cell viability was measured, and then the cells were cultured to assess their PDT. Generalized linear models test was used to compare cell viability between post-thaw, post-propagation, post-radiation, post-culture post-radiation, and control and between radiation dose groups. Kruskal-Wallis test assessed PDT between various radiation doses in post-radiation groups. Wilcoxon test was used to assess PDT between pre-radiation and post-radiation groups. Results: Mean confluence period of adipose MSCs post- irradiation was 4.33 days. There was no statistically significant difference in MSC viability after X-ray exposure between pre- and post-irradiation groups (p=0.831). There was no correlation between post-irradiation viability and radiation dose (p=0.138, r=0.503). There were no significant differences in PDT between pre- and post-culture post-irradiation groups and between various radiation doses in post-irradiation groups (p=0.792). Conclusion: MSC viability and PDT were not influenced by radiation exposure up to 32.34 mgray.